Spatio-temporal variability in benthic exchanges at the sediment-water interface of a shallow tropical coastal lagoon (south coast of Gulf of Mexico). (5th March 2019) - Grenz, Christian; Moreno, Montserrat Origel; Soetaert, Karline; Denis, Lionel; Douillet, Pascal; Fichez, Renaud
Abstract: The sediment in Laguna de Términos, the largest and shallowest system in the Southwest portion of the Gulf of Mexico features a broad range of ecological and hydrobiological characteristics driven by annual weather cycles (dry and wet seasons), causing large salinity gradients during the wet season due to large river discharges. Four sampling campaigns were carried out during the wet and the dry seasons in 2009 and 2010 on a selection of 13 out of 35 stations. Measurements of Sediment Oxygen Demand (SOD) and nutrient fluxes at the sediment-water interface were performed using lab incubations with 15 cm diameter sediment cores. SOD fluctuated between 1327 ± 161 and 2248 ± 359 μmol m −2 h −1 for dry and wet seasons respectively. Silicate effluxes were also significantly higher during the wet seasons (89.4 ± 15.9 μmol m −2 h −1 ) than during the dry season (46.5 ± 11.4 μmol m −2 h −1 ). PO4 fluxes were low all over the study period without seasonal trend. No significant difference was measured for DIN fluxes but there was a tendency for DIN uptake during the wet season (−2.9 ± 18.8 μmol m −2 h −1 ) and conversely an efflux during the dry season (24.3 ± 7.3 μmol m −2 h −1 ). SOD correlated to organic matter and chloropigment content of the sediments while silicate fluxes responded to enhanced chloropigments in the sediments. During both seasons, total benthic nutrient fluxes overwhelmed largely riverine inputs and benthic carbon mineralization rates approximated a significant proportion of the pelagic organic carbon production. We conclude that benthic processes in Laguna de Términos are largely driven by weather variability and that they contribute substantially to carbon and nutrient budgets in this shallow sub-tropical system.